2012
DOI: 10.1242/jeb.057562
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the rebound of the body in backward human running

Abstract: SUMMARYStep frequency and energy expenditure are greater in backward running than in forward running. The differences in the motion of the centre of mass of the body associated with these findings are not known. These differences were measured here on nine trained subjects during backward and forward running steps on a force platform at 3-17kmh -1. In contrast to previous reports, we found that the maximal upward acceleration of the centre of mass and the aerial phase, averaged over the whole speed range, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…These results contrast with our second hypotheses which stated that vertical and joint stiffness in both limbs would increase with an increase in running speed. The lack of main effect of running speed on K vert , K knee and K ankle might be due to the lower running speeds and smaller range of speeds in the present study compared with previous studies (Cavagna et al, 2005, 2012; He et al, 1991; Kuitunen et al, 2002; McGowan et al, 2012; Morin et al, 2005, 2006). Otherwise, small sample size might lead the invariant lower extremity stiffness according to the running speeds in the present study.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…These results contrast with our second hypotheses which stated that vertical and joint stiffness in both limbs would increase with an increase in running speed. The lack of main effect of running speed on K vert , K knee and K ankle might be due to the lower running speeds and smaller range of speeds in the present study compared with previous studies (Cavagna et al, 2005, 2012; He et al, 1991; Kuitunen et al, 2002; McGowan et al, 2012; Morin et al, 2005, 2006). Otherwise, small sample size might lead the invariant lower extremity stiffness according to the running speeds in the present study.…”
Section: Discussioncontrasting
confidence: 85%
“…Several studies have shown that vertical stiffness increases with an increase in running speed (Cavagna et al, 2005, 2012; He et al, 1991; Kuitunen et al, 2002; McGowan et al, 2012; Morin et al, 2005, 2006). In a multijointed system, K vert further depends on a combination of the torsional stiffnesses of the joints (joint stiffness; K joint , Kuitunen et al, 2002; Butler et al, 2003; Farley et al, 1998; Farley and Morgenroth, 1999; Hobara et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, backward walking and running are energetically 28-78% and 15-34%, respectively, more demanding than their forward locomotion equivalents, as a result of greater external work done against gravity at low speeds and greater internal work caused by an increased step frequency and greater mass-specific vertical stiffness of the bouncing system at high speeds (Cavagna et al, 2012;Flynn et al, 1994;Vilensky et al, 1987;Williford et al, 1998;Winter et al, 1989). The elevated metabolic demands associated with backward movement likely derive from the relative terrestrial rarity of this locomotor mode.…”
Section: Introductionmentioning
confidence: 99%
“…Forward running is often understood in terms of a spring mass model by which muscles are stretched and eccentric energy is absorbed and converted to propulsive energy through the tendons and connective tissue(6). Alternatively, BR more closely reflects a pendulum action whereby the muscle and tendon length remains relatively constant upon foot-ground contact and propulsion is produced primarily through a contractile movement(8,9). Concentric-dominant exercises offer a potentially useful training tool, which may negate or mitigate muscle damage, soreness, fatigue, and inflammation associated with eccentric movements(26).…”
mentioning
confidence: 99%
“…along with increased demand on the concentric functioning of muscles have been postulated to influence the specific metabolic responses to BR(8,9). Practically, this means that athletes who are either injured, or under a high training load, can include BR into their programme to stimulate metabolic responses similar to FR with fewer repetitions.7.3 The How: Integrated ProgrammingGiven the highlighted research into why a strength and conditioning coach may wish to implement BR as an acute or chronic training stimulus for athletes, it is important to understand how BR may be integrated as an effective training practice.…”
mentioning
confidence: 99%